2008
DOI: 10.1080/10408440802273164
|View full text |Cite
|
Sign up to set email alerts
|

Negative Confounding in the Evaluation of Toxicity: The Case of Methylmercury in Fish and Seafood

Abstract: In observational studies, the presence of confounding can distort the true association between an exposure and a toxic effect outcome if the confounding variable is not controlled either in the study design or the analysis phase. While confounding is often assumed to occur in the same direction as the toxicant exposure, the relationship between the benefits and risks associated with fish and seafood consumption is a classic example of negative confounding: the exposure to methylmercury occurs from fish and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(65 citation statements)
references
References 130 publications
1
63
0
1
Order By: Relevance
“…Additionally in the Fishermen study, potential negative confounding (Choi et al, 2008) was controlled for by adjusting means across omega-3 PUFA tertiles for environmental contaminants and vice versa. However, the models were stable regardless of large number of covariates, and the adjustments did not essentially change the results.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally in the Fishermen study, potential negative confounding (Choi et al, 2008) was controlled for by adjusting means across omega-3 PUFA tertiles for environmental contaminants and vice versa. However, the models were stable regardless of large number of covariates, and the adjustments did not essentially change the results.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent analyses based on Faroe and Seychelles cohort data have demonstrated an increase of the methylmercury adverse effects after adjusting the models for these potentially beneficial factors. 1,4,9 Furthermore, socioeconomic factors may be more favorable in mothers who consume more fish, especially larger fish that may contain higher toxicant concentrations. 7 If such negative confounding is not taken into proper account in the data analysis, the toxicity will be underestimated.…”
mentioning
confidence: 99%
“…If the toxicant is measured with a greater imprecision than the confounder, the effect of the former will generally be biased toward the null. [9][10][11] Within a population, the apparent effects of risk factors will not be evenly distributed. Studies of genetic factors in intelligence have shown the strongest effect in upper social strata, where adverse risk factors may be less important than inheritance and more evenly distributed.…”
mentioning
confidence: 99%
See 2 more Smart Citations